2013
DOI: 10.1104/pp.112.211391
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Trehalase Gene AtTRE1 Leads to Increased Drought Stress Tolerance in Arabidopsis and Is Involved in Abscisic Acid-Induced Stomatal Closure    

Abstract: Introduction of microbial trehalose biosynthesis enzymes has been reported to enhance abiotic stress resistance in plants but also resulted in undesirable traits. Here, we present an approach for engineering drought stress tolerance by modifying the endogenous trehalase activity in Arabidopsis (Arabidopsis thaliana). AtTRE1 encodes the Arabidopsis trehalase, the only enzyme known in this species to specifically hydrolyze trehalose into glucose. AtTRE1-overexpressing and Attre1 mutant lines were constructed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(121 citation statements)
references
References 74 publications
(107 reference statements)
5
116
0
Order By: Relevance
“…However, in most cases the enhanced stress tolerance did not appear to be linked to increased trehalose accumulation. Indeed, the opposite was true for Arabidopsis tre1 mutants that lacked trehalase activity and had moderately elevated trehalose levels but were more sensitive to drought than wild-type plants (Van Houtte et al, 2013). Thus, we need to search for alternative explanations for the beneficial effects of manipulating trehalose metabolism on stress tolerance and for understanding the role of trehalose metabolism in endogenous responses to abiotic stresses.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…However, in most cases the enhanced stress tolerance did not appear to be linked to increased trehalose accumulation. Indeed, the opposite was true for Arabidopsis tre1 mutants that lacked trehalase activity and had moderately elevated trehalose levels but were more sensitive to drought than wild-type plants (Van Houtte et al, 2013). Thus, we need to search for alternative explanations for the beneficial effects of manipulating trehalose metabolism on stress tolerance and for understanding the role of trehalose metabolism in endogenous responses to abiotic stresses.…”
Section: Tre6p and Abiotic Stress Tolerancementioning
confidence: 99%
“…In Arabidopsis, the AtTPS1 gene is highly expressed is guard cells (Gómez et al, 2010), and these cells are one of the few examples where the AtTPS1 protein is abundant enough to have been detected in an untargeted proteomic analysis (Zhao et al, 2008). Expression of AtTPPG and AtTREHALASE1 (AtTRE1; encoding the only known trehalase in Arabidopsis) is also particularly prominent in guard cells, and both genes are induced by ABA, which plays a key role in regulation of stomatal conductance Van Houtte et al, 2013). The Arabidopsis tps1-12 mutant, which carries a weak allele of the AtTPS1 gene, has a smaller stomatal aperture than wild-type plants (Gómez et al, 2010).…”
Section: Tre6p and Regulation Of Stomatal Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…It seems that ABA directly participates in the upregulation of AtTRE and AtTRE1 is involved in the regulation of ABA signaling in plants. 30 In addition, during the pathogenic interaction between Plasmodiophora brassicae and Arabidopsis thaliana a marked AtTRE1 upregulation was also reported. 12 In contrast, downregulation of PvTRE1 in Phaseolus vulgaris root nodules had a direct role into carbon partitioning, increased nodule biomass and bacteroid viability.…”
Section: Trehalasesmentioning
confidence: 99%
“…Previous studies have demonstrated that resistance could be improved by importing GPAT cDNA (Yokoi et al, 1998;Sui et al, 2007;Gupta et al, 2013;Mizoi and Yamaguchi-Shinozaki, 2013), but current studies are mostly focused on individual genes that can improve cold resistance in plants (Macková et al, 2013;Van Houtte and Vandesteene, 2013;Wang et al, 2014;Yadav et al, 2014), while associations between the promoters of these genes and resistance have not yet been reported. Plant promoters play an important role in the regulation of gene expression in plants (Kim et al, 2013;Reynolds et al, 2013).…”
Section: Introductionmentioning
confidence: 99%